2022
DOI: 10.1007/s11273-021-09852-2
|View full text |Cite
|
Sign up to set email alerts
|

Egg banks in dryland wetlands provide information on the diversity and vulnerability of branchiopod communities along a longitudinal aridity gradient

Abstract: Continued degradation of temporary wetlands and rapidly declining freshwater biodiversity call for identification of vulnerable species as targets for conservation and management efforts. Branchiopod crustaceans are endemic to temporary waters and rely on banks of drought-resistant eggs in the sediment for survival across dry seasons. These egg banks are like archives to biologists and allow them to estimate population status and resilience, without the need to sample active communities. Such an approach has, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…This disparity was accredited to the shorter hydroperiod and simpler geomorphology of the treed swamps which reduced species replacement during the periods in which branchiopods and insects were dominant. The overall effect, as in the study by Meyer-Milne et al (2022), is a reduction in biodiversity with aridity. In extreme cases of prolonged drought, it is possible that these systems may even become terrestrialised (cf., Sandi et al 2019), with permanent loss of wetlands.…”
Section: Synthesis Of Articles and Emergent Research Themesmentioning
confidence: 79%
See 2 more Smart Citations
“…This disparity was accredited to the shorter hydroperiod and simpler geomorphology of the treed swamps which reduced species replacement during the periods in which branchiopods and insects were dominant. The overall effect, as in the study by Meyer-Milne et al (2022), is a reduction in biodiversity with aridity. In extreme cases of prolonged drought, it is possible that these systems may even become terrestrialised (cf., Sandi et al 2019), with permanent loss of wetlands.…”
Section: Synthesis Of Articles and Emergent Research Themesmentioning
confidence: 79%
“…For instance, in their study of branchiopod communities in temporary wetlands of South Africa, Meyer-Milne et al ( 2022 ) found that fewer branchiopod eggs were stored in wetland soil sub-surface layers as aridity increased. This suggests that although egg and seed stores might provide an opportunity for species to survive droughts, sustained increases in aridity as a consequence of climate change may exceed species resilience.…”
Section: Synthesis Of Articles and Emergent Research Themesmentioning
confidence: 99%
See 1 more Smart Citation